2013
DOI: 10.1016/j.jpainsymman.2012.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Delivery Strategies to Optimize Resource Utilization and Performance Status for Patients With Advanced Life-Limiting Illness: Results From the “Palliative Care Trial” [ISRCTN 81117481]

Abstract: A single case conference added to current specialized community-based palliative care reduced hospitalizations and better maintained performance status. Comparatively, patient/caregiver education was less effective; GP education was not effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
78
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 83 publications
(84 citation statements)
references
References 36 publications
2
78
0
4
Order By: Relevance
“…However, the outcomes could be worth the eff ort. For example, two randomised controlled trials have shown that just one case-conference involving a PCP and a specialist palliative-care team confers benefi ts, including improved patient performance capacity, reduced hospital admissions and referrals to the emergency department, 249 and improved quality of life in the patient's last month of life. 250 PCPs also have a role in caring for the carers of people with advanced cancer.…”
Section: Facilitating Multidisciplinary Palliative Carementioning
confidence: 99%
“…However, the outcomes could be worth the eff ort. For example, two randomised controlled trials have shown that just one case-conference involving a PCP and a specialist palliative-care team confers benefi ts, including improved patient performance capacity, reduced hospital admissions and referrals to the emergency department, 249 and improved quality of life in the patient's last month of life. 250 PCPs also have a role in caring for the carers of people with advanced cancer.…”
Section: Facilitating Multidisciplinary Palliative Carementioning
confidence: 99%
“…Recognizing the significant supportive care needs among cancer patients and the role that palliative care plays in addressing these needs [1][2][3][4], multiple national and international professional organizations have called for increased integration of oncology and palliative care [5][6][7][8]. Since 2004, the European Society for Medical Oncology (EMSO) offered an incentive program of 'ESMO designated centers of integrated oncology and palliative care' based on 13 criteria that focused on the palliative carerelated processes, education, and research; however, these criteria did not explicitly include formal clinical structures [6].…”
Section: Introductionmentioning
confidence: 99%
“…Understanding and considering this clinical entity is of importance for how we prepare and assist patients for the end of their lives, evaluate the impact a sudden death in the setting of a life-limiting illness has on the palliative care may help patients and families by setting realistic and desirable outcomes for the future and proactively creating crisis management plans (30). As part of this role, it is critical for clinicians to begin to explore ways to educate and help patients/families adapt to the idea of sudden death in the face of a progressive life-limiting illness.…”
mentioning
confidence: 99%